Anthocyanin yield and skin softening during maceration, as affected by vineyard row orientation and grape ripeness of Vitis vinifera L. cv. Shiraz. (1st May 2015) - Giacosa, Simone; Marengo, Fabio; Guidoni, Silvia; Rolle, Luca; Hunter, Jacobus J.
Highlights: Anthocyanin yield and skin softening evaluation during maceration of Shiraz grapes. Decrease of the grape anthocyanin content and mechanical properties during ripening. Reduction in the crushed berry skin break force/energy parameters during maceration. Vineyard row orientation showed little effect in grapes and wines composition. Percentage increase of cinnamoyl-glucoside forms in riper grapes was detected. Abstract: Anthocyanin and mechanical properties were evaluated on Shiraz grapes, picked from both sides of North–South and East–West vineyard row orientations at two harvest dates. Wines were made from each combination. The evaluation and evolution of crushed skin mechanical properties during maceration–fermentation, as also affected by grape ripeness, are shown for the first time. No significant differences in anthocyanin content were found in the grapes between the two vineyard row orientations. However, a significant decrease in anthocyanins and berry skin break force (also referred as skin hardness or strength) was found between the two harvest dates. During maceration, a reduction in the crushed berry skin break force of more than 15% occurred. The intact berries and macerated skins showed similarity in skin break energy values. The anthocyanin profile of the grapes and of the wines prominently displayed malvidin forms, changed mainly by the ripeness level of the grapes.